IMPLEMENTASI RAPID APPLICATION DEVELOPMENT DALAM PENULISAN ULANG TOTAL PHP VERSION MANAGER ASDF-PHP - Kosdiana Kosdiana; Desi Diana; Mohamad Saefudin (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
This study discusses the application of the Rapid Application Development (RAD) methodology in a complete rewrite of the asdf-php plugin by integrating the php-build build engine. Previous versions of the asdf-php plugin faced various challenges, such as high code complexity and installation failures on modern operating systems. However, this plugin plays a crucial role in supporting the PHP ecosystem. Therefore, improvements were needed through a more effective development approach. In this study, the authors applied the RAD methodology to accelerate the software development process. The stages involved included requirements planning, user design, construction, and the final implementation (cutover) phase. This approach enabled an iterative and adaptive development process, facilitating adjustments to system requirements. The result of this study is a new plugin infrastructure that functions as an efficient wrapper over php-build. Automated testing demonstrated improved installation reliability and overall system stability. Furthermore, the application of the RAD methodology proved effective in producing open source software that is more efficient, easier to maintain, and able to leverage mature community components.